Study of Stunting Determinants in the Highest-Prevalence Area of Southeast Sulawesi, Indonesia - Venia Oktafiani; Suci Dwi Yanti; Linda Ayu Rizka Putri (Jurnal Ilmiah Kesehatan (JIKA), 2026)
While national interventions like the Free Nutritious Meal Program and breastfeeding promotion have shown regional success in Southeast Sulawesi, Buton District experiences a paradoxical rise in stunting. This study aimed to analyze the determinants of stunting in this high-prevalence area. A case-control study was conducted in the 6 subdistricts of Buton District from July to September 2025, involving 106 mothers of children aged 6–59 months (53 stunted and 53 non-stunted). Bivariate and multivariate logistic regression were used to identify factors associated with stunting. Multivariate analysis showed that younger age (aOR = 0.92; 95% CI: 0.87–0.97; p =  0.002), primigravida status (aOR = 0.07; 95% CI: 0.00–0.78; p =  0.031), higher maternal education (aOR = 0.01; 95% CI: 0.00–0.26; p =  0.004), and higher household income (high: aOR = 0.01; 95% CI: 0.00–0.13; p =  0.001; medium: aOR = 0.05; 95% CI: 0.00–0.92; p =  0.044) were protective against stunting. Other variables, including exclusive breastfeeding, maternal history of chronic energy deficiency, iron supplementation, drinking water treatment, and household size, were not significant. The model demonstrated good explanatory power (Nagelkerke R² = 0.665) and fit (Hosmer–Lemeshow = 0.830).Maternal education and household income are key determinants of stunting in Buton District. Interventions should target maternal knowledge, economic empowerment, and support for multigravida mothers to reduce stunting in high-risk areas.